Pengaruh Penerapan Prinsip-Prinsip Good Governance dan Budaya Organisasi terhadap Kinerja Keuangan - Dhyana Putra, I Gede; Asri Dwija Putri, I G. A. M. (E-Jurnal Akuntansi, 2020)
This study aims to examine the effect of applying the principles of good governance and organizational culture on financial performance. This research was conducted at the Village Credit Institution (LPD) in Gianyar Regency. The sampling method uses proportionate stratified random sampling. The number of samples of this study were 25 LPDs spread in each district in Gianyar Regency. Data collection was carried out through a survey approach with a questionnaire method and also data collection in the form of LPD financial statements in 2018. The data analysis technique used was the Multiple Linear Regression Analysis test. Based on the test results, it was found that there was a positive influence from the application of good governance principles and organizational culture to the financial performance of LPD in Gianyar Regency. Keywords: Good Governance; Organizational Culture; Financial Performance; Village Credit Institutions.